Synergies and embeddedness of the State in society: The alternative economic policy of the Regional Government of San Martín - Kaulard, Anke (2018)
The «Miracle of San Martín» in the Peruvian Amazon is a metaphor that is known nationally and internationally, for the recovery of state order in a region that has been convulsed by terrorism and drug trafficking. With the lens of historical and social neo-institutionalism, this article explores economic policies, synergies and actors of «alternative development» in San Martín, who have been offered an alternative to coca by the implementation of organic and fair trade cocoa chains. This study finds that the construction of organic and fair trade cocoa chains, commonly perceived as relatively successful because of the intervention of international cooperation agencies, has been possible in fact due to two different key factors. On the one hand, the development of a proper and innovative landmark of a modernized regional government, that is permitted to be «developmental» in a mostly neoliberal context in Peru where direct state intervention in the economy is usually restricted. On the other hand, the rather unusual continuity of regional government´s staff in different government periods and their professionalization as an agricultural «green policy think and action tank» together with the formation of technical experts called «tigers», who contributed to a stable policy of the sustainable global value chains and their implementation.